Understanding the recovery of a secondary forest in Singapore through the lenses of traits and demography - Gan, Jessie Hui Sze (Nanyang Technological University, 2019)
Secondary forests are expanding rapidly in the tropics and simultaneously, their role in restoring functions and features of the primary forest they are replacing is increasingly recognized. However, despite the importance of tropical forest recovery in restoring ecosystem services and maintaining biodiversity once present in the original tropical forests, this process is poorly understood. In this study, I examined the recovery of a tropical secondary forest in Singapore using trait- and demography-based approaches in two separate field studies. Specifically, I addressed: a) the extent to which four plant functional traits (leaf mass per area, leaf thickness, leaf toughness and wood density) explained interspecific colonization successes of 15 non-pioneer species in secondary forest during forest recovery, b) if functional traits of successfully colonizing species exhibited similar trends when compared to their respective less successful congener for six species pairs and c) how the species composition and richness of seedlings in recovering secondary forest compared to those of larger size classes in both primary and secondary forests. In the first part of the study, I found very weak correlations between colonization success in secondary forest and the selected functional traits, where seemingly inconsistent trends were observed across the species pairs. In particular, significant differences in divergent directions were detected for most of the functional traits within each of the six congeneric species pairs. My overall results did not agree with the plant ecological strategy continuum based on resource acquisition (‘resource-acquisitive’ versus ‘resource-conservative’) that has often been linked to recovering forests. In the second part of the study, a seedling census also revealed signs of slow recovery in the secondary forest with high percentage overlaps between species of seedlings and the larger tree size classes. Findings from this study highlighted the importance of incorporating functional traits from different niche axes and contexts in order to fully capture and understand plant ecological strategies. They also reveal the potential influence of stochastic processes such as dispersal limitation on the colonization success of non-pioneer species in the secondary forest and masting events on seedling recruitment. Finally, they also provide additional evidence for the slow recovery of the secondary forest in BTNR. This calls for more robust and targeted investigation on the factors slowing natural forest regeneration in BTNR to supplement management strategies for the speeding up of the process.